Trade policy and economic welfare - Corden, W. M. (Oxford : Clarendon Press, 1974)
This book expounds the normative theory of trade policy and complements the author's theory of protection, which dealt with the positive theory. It includes discussion of static and dynamic arguments for protection; effects of trade policies on income distribution, monopoly, x-efficiency, foreign investment and capital accumulation; protection of advanced-technology industries; the choice between tariffs and subsidies as methods of protection
Includes bibliographical references and indexes.
ijb, 15/01/2019
Loans
Keywords: Free trade; Protectionism; Commercial policy; Industrial policy